ANALYSIS OF NUTRITIONAL AND CHEMICAL PROPERTIES OF MELGHAT HONEY FOR QUALITY CHARACTERISTICS - KSHITIJ N. SHAH (The Journal of Research ANGRAU, 2022)
In this study, the Melghat honey samples were analyzed for their nutritional and chemicalproperties. The samples were collected from four different locations in Melghat in the year 2019.A number of factors such as carbohydrates, energy, sugar profile, protein, HMF, acidity, iron,calcium, and sodium were detected. The data was compared to published data and specificationsgiven in the Bureau of Indian Standards (BIS) manual. The data confirmed that the honey samplesfrom Melghat fell into the category of special grade as specified by BIS. It is concluded that theMelghat honey is of outstanding value, with good healing and antimicrobial properties. It is veryless susceptible to fermentation, very pure, and unadulterated. There is a requirement for morestudies to discover the assortment of properties of Melghat honey for its commercialization.